2020
DOI: 10.1177/2633366x20954875
|View full text |Cite
|
Sign up to set email alerts
|

Optimization design of low-density and high-strength ceramic proppants by orthogonal experiment

Abstract: This study mainly focused on an orthogonal optimization design of low-density and high-strength ceramic proppants prepared by low-grade bauxite and feldspar that met the standard requirements. The orthogonal experimental design of L25 (53) was employed to study the significance sequence of three factors, including milling time of bauxite, milling time of feldspar, and sintering temperature. The results show that the particle size of feldspar is the most important factor for the performance of the proppants. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The L9(3 4 ) orthogonal experiments were designed and analysed using the orthogonal assistant software (Li and Hao 2020; Duan et al . 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The L9(3 4 ) orthogonal experiments were designed and analysed using the orthogonal assistant software (Li and Hao 2020; Duan et al . 2023).…”
Section: Methodsmentioning
confidence: 99%
“…The L9(3 4 ) orthogonal experiments were designed and analysed using the orthogonal assistant software (Li and Hao 2020;Duan et al 2023). Orthogonal experiment is a method of using an orthogonal table that has been created to arrange experiments and perform data analysis.…”
Section: Orthogonal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the 21st century, scholars believed that the presence of oxides in raw materials decreases the strength of ceramic proppants, 35 but recent studies have found that oxides can help form the skeleton structure of the mullite matrix phase from Al 2 O 3 and SiO 2 , and the liquid phase from the high‐temperature melting of these oxides can fill the pores during the sintering process, both of which are beneficial to enhancing the strength of ceramic proppants. With regard to the sintering additive of silica‐rich minerals (mainly feldspar minerals), this paper does not elaborate this matter anymore because its nature is similar to the addition of coal gangue 63–65 . On the basis of the strengthening mechanism, sintering additives are divided into two categories, namely, high‐temperature liquid‐phase sintering additives and lattice distortion sintering additives.…”
Section: Effects Of Additives On Coal Gangue Ceramic Proppantsmentioning
confidence: 99%
“…With regard to the sintering additive of silica-rich minerals (mainly feldspar minerals), this paper does not elaborate this matter anymore because its nature is similar to the addition of coal gangue. [63][64][65] On the basis of the strengthening mechanism, sintering additives are divided into two categories, namely, hightemperature liquid-phase sintering additives and lattice distortion sintering additives.…”
Section: Sintering Additivesmentioning
confidence: 99%